2003
DOI: 10.1038/sj.embor.embor866
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic‐cell‐specific ICAM3‐grabbing non‐integrin is essential for the productive infection of human dendritic cells by mosquito‐cell‐derived dengue viruses

Abstract: Dengue virus (DV) is a mosquito‐borne flavivirus that causes haemorrhagic fever in humans. DV primarily targets immature dendritic cells (DCs) after a bite by an infected mosquito vector. Here, we analysed the interactions between DV and human‐monocyte‐derived DCs at the level of virus entry. We show that the DC‐specific ICAM3‐grabbing non‐integrin (DC‐SIGN) molecule, a cell‐surface, mannose‐specific, C‐type lectin, binds mosquito‐cell‐derived DVs and allows viral replication. Conclusive evidence for the invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
398
1
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 447 publications
(416 citation statements)
references
References 35 publications
12
398
1
5
Order By: Relevance
“…However, this may not represent the sole means for glycosylated flaviviruses to interact with DC-SIGN as it does not account for the observed impact of polymorphisms on TBEV infection (Barkhash et al, 2012) or the ability of WT glycosylated WNV to use it as a receptor (Davis et al, 2006b;Martina et al, 2008), as both viruses only contain the N154 glycan. It may be that high-mannose glycosylation of arthropodderived flavivirus virions facilitates better DC-SIGN interaction with the N153/4 residue (Davis et al, 2006b;Navarro-Sanchez et al, 2003).…”
Section: Glycan Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this may not represent the sole means for glycosylated flaviviruses to interact with DC-SIGN as it does not account for the observed impact of polymorphisms on TBEV infection (Barkhash et al, 2012) or the ability of WT glycosylated WNV to use it as a receptor (Davis et al, 2006b;Martina et al, 2008), as both viruses only contain the N154 glycan. It may be that high-mannose glycosylation of arthropodderived flavivirus virions facilitates better DC-SIGN interaction with the N153/4 residue (Davis et al, 2006b;Navarro-Sanchez et al, 2003).…”
Section: Glycan Modificationmentioning
confidence: 99%
“…Dendritic cells and macrophages express DC-SIGN in humans, with homologous Ca 2+ -dependent (C-type) lectin receptors (CLRs) in mice displaying distinct patterns of expression (Koppel et al, 2005;Kwan et al, 2008;Navarro-Sanchez et al, 2003;Tassaneetrithep et al, 2003). This lectin receptor recognizes high-mannose glycans and fructose-containing Lewis x antigens (Koppel et al, 2005) and has been demonstrated as a primary cellular attachment moiety for DENV and WNV (Davis et al, 2006a, b;Kwan et al, 2008;Lozach et al, 2005;Martina et al, 2008;Navarro-Sanchez et al, 2003;Tassaneetrithep et al, 2003;Wang et al, 2011). Polymorphisms within the promoter encoding DC-SIGN have also been associated with severe TBEV infection in humans (Barkhash et al, 2012).…”
Section: Glycan Modificationmentioning
confidence: 99%
“…Several types of cellular receptor have been identified for DENV: highly sulfated heparan sulfates (hsHS) (Chen et al, 1997), the lectins DC-SIGN and L-SIGN (Navarro-Sanchez et al, 2003;Tassaneetrithep et al, 2003) and the lamininbinding protein (Thepparit & Smith, 2004;Tio et al, 2005). The structure of the complex between DENV and the carbohydrate-recognition domain of DC-SIGN has et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…La lectine de surface DC-specific ICAM-3-grabbing nonintegrin (DC-SIGN ou CD209) est un récepteur d'attachement au VDEN via la reconnaissance de la glycoprotéine E de l'enveloppe virale. Cette interaction est indispensable à l'infection productive des DC [5,6]. Du fait de son rôle clé dans les premiè-res étapes de l'infection, nous avons donc considéré le gène DC-SIGN comme un candidat pouvant intervenir dans la variabilité inter-individuelle du risque d'infection par le DVEN ou des manifestations cliniques [7].…”
Section: Association D'un Variant Génétique Du Récepteur D'attachemenunclassified